Monthly Pattern Of Inseminations And Reproductive Health Disorders In Dairy Bovines Of Middle Gujarat - Hadiya, K.K.; Patel, J.A.; Shah, R.G.; panchal, M.T.; Dhami, A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A total of 2281 and 8872 inseminations, and 1907 and 13568 sexual health control cases attended in cattle and buffaloes, respectively, over last 14 years at College Gynaecology Clinic in Anand were evaluated to know the monthly pattern of breeding and reproductive health disorders faced by these dairy animals in the agro-climatic conditions of middle Gujarat together with yearly trend of these dual services being offered to the dairy farmers of the region at the College. The monthly trends of both insemination and reproductive health control (RHC) cases in cattle were almost consistent throughout the year, except a slight decline in March-April, whereas buffaloes showed clear seasonality in both inseminations and RHC cases, with maximum 70.65 % and 62.20 % being attended between September and February months of the year (peak being December-January, 30.32 and 24.18 %), and the least 6.80 and 10.16 % during May-June. Further, the yearly trends of annual AI and RHC cases worked out for the past 14 years clearly revealed a gradual and consistent decline in number/per cent of the total cases (AI 13.25% to 1.95%; RHC 14.40% to 1.73%) being attended at College from 1999 to 2012, the decline being drastic overall last 5 years. The overall distribution of pooled RHC cases showed the incidence of functional ovaries (suboestrum) as 24.90 %, inactive ovaries (true anoestrum) 25.76 %, pregnancy diagnosis 13.89 %, uterine infections (endometritis, metritis, pyometra) 18.45 %, repeat breeding 5.35 %, infantile genitalia 4.65 %, ovarian disorders 1.20 %, cervical disorders 2.33 %, abortion, mummification, maceration etc 1.29 %, and genital prolapse, torsion, dystocia, retained placenta, etc together 2.18 %. The occurrence of suboestrum and anoestrum was more common during summer due to malnutrition, heat stress and seasonality of breeding. Similarly, uterine infections were more common during peak seasons of breeding and calving due to unhygienic conditions. Further, the major reasons for the decline in number of cases at College Clinic are; rapid and extensive urbanization, depletion of large animal population from the surrounding pockets for miles due to conversion of agricultural lands into built up societies, development of fast track roads /circles and increased traffic problems in bringing large animals to the college on foot, and even prompt availability of doorstep services for AI and health coverage by private as well as co-operative sectors, together with increased awareness among dairy animal keepers.
Keywords: Monthly pattern; Yearly trend; Artificial insemination; Sexual health control; Cattle; Buffalo; Middle Gujarat